Alternativas para la industrialización de barras energéticas a partir de la quinua (Chenopodium quínoa), amaranto (Amaranthus hypochondriacus) y chía (Salvia hispánica l.) con tres tipos de jarabes: miel de agave, miel de abeja y glucosa en los laboratorios académicos de la carrera de ingeniería agroindustrial de la Universidad Técnica de Cotopaxi en el período 2015 - Casamen Velasco, Luis Armando (2015)
The present investigation had as objective to develop an energy counters from quinoa (Chenopodium quimoa), amaranth (Amaranthus hypochondriacus) an chia (salvia hispánica) whit three types of syrup; honey agave, honey bee and glucose with other raw materials;they were oats, peanut, crispy rice and raisins of this way obtaining a product with high nutritional value its protein content of 8.34%, followed by the fat at a rate of 4.20%, fiber 2.01%, calcium 19.46 mg/ 100g, energy 356,76 Kcal/100g and finally total carbohydrates with 71.40%. It has been made the organoleptic analysis to defferent treatments where it evaluated the color, smell, taste, tecture and acceptability, this survey was realized to 100 students of the Education Unit Alejandro Dávalos Calle, whit the data obtained the tabulation was done in the statistical program Infostat and Exel applying a scheme of analysis of variance with the design of randomized complete blocks (DBCA) in factorial arrangement of 3*3.